2016
DOI: 10.1016/j.ijfatigue.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Through thickness property variations in friction stir welded AA6061 joint fatigued in very high cycle fatigue regime

Abstract: b s t r a c tUltrasonic fatigue tests were performed on friction stir welded AA6061 joint to investigate very high cycle fatigue (VHCF) behaviors. As a result, almost all the fatigue cracks are initiated from local plastic slip markings around the boundary between thermo-mechanically affected zone and heat affected zone. The fatigue strength decreases from the top to root of the welded joint, owing to the variation of plastic deformation history and temperature distribution through the thickness. In fractograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
3
24
1
Order By: Relevance
“…In other words, the formation of these zones was finished before the occurrence of a stable extended crack on the meaning of fracture mechanics. Similarly, the special morphology around the crack initiation site is also observed in the VHCF study of AA 6061 FSW joint [16], and it was reported that the formation of these zones consumes over 98% of total fatigue life in the VHCF range. The formation mechanism of the flat zones is still controversial and unclear.…”
Section: Fatigue Crack Propagation Thresholdsupporting
confidence: 56%
See 2 more Smart Citations
“…In other words, the formation of these zones was finished before the occurrence of a stable extended crack on the meaning of fracture mechanics. Similarly, the special morphology around the crack initiation site is also observed in the VHCF study of AA 6061 FSW joint [16], and it was reported that the formation of these zones consumes over 98% of total fatigue life in the VHCF range. The formation mechanism of the flat zones is still controversial and unclear.…”
Section: Fatigue Crack Propagation Thresholdsupporting
confidence: 56%
“…Generally, the welding processing significantly alters the local material properties; hence the local mechanical behaviors are tied directly to the heterogeneous microstructure [32]. Accordingly, the resistance to fatigue crack initiation across the weld is also determined by local property distributions associated with the inhomogeneous structure [16]. In this test, the location of fatigue crack initiation site along with the fatigue life is presented in Figure 8(a).…”
Section: Fatigue Crack Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…can endure a fatigue life larger than 10 7 or 10 8 loading cycles, and even up to 10 10 ~ 10 11 life cycles of endurance in some vital cases [6][7][8]. So the understanding of fatigue behaviors in the very high cycle (VHC) regime has attracted an increasing number of investigators in the fatigue research field.…”
Section: Introductionmentioning
confidence: 99%
“…In very high cycle fatigue (VHCF) range, fatigue life of the FSW joint was limited by surface crack nucleation, which accounted for over 98% of the total fatigue life. 10 Therefore, it is conceivable that surface enhancement of the friction stir welds probably bring a considerable improvement of the VHCF strength.…”
mentioning
confidence: 99%